ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI HITUNG PADA BILANGAN PECAHAN CAMPURAN - Zalima, Errina Ida; Njanji, Ferdianus Panggar; Lasmiatik, Lasmiatik; Agustina, Leni; Dela, Maria; Ambarawati, Mika (Universitas Insan Budi Utomo, 2020)
This study describe the analysis of the difficulty of students in completing problem arithmetic operations on mixed numbers class VI MI Darussalam Malang. This type of research is a descriptive study with a qualitative approach. The subjects of this study are students of class VI MI Darussalam Malang with high, medium, and low grades. The results showed that: (1) students in the high and medium grades did not have difficulty in changing mixed fractions to ordinary fractions, however students in the low grade category have difficulty in converting mixed fractions to ordinary fractions; (2) students in the high grade category have no difficulty equating the denominator, however students in the medium and low grade categories have difficulty in equating the denominator of fractions; (3) students with all three categories of high, medium, and low grades have difficulty in calculating fraction operations with three mixed numbers; and (4) students in the high, medium, and low grade categories have difficulty completing the mixed fraction counting operation.